2002
DOI: 10.1207/s15328015tlm1402_10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Performance Assessment and Interactive Video Teleconferencing: An Iterative Exploration

Abstract: We feel confident in recommending IVT as a viable option for involving community preceptors in high-stakes testing and with other campus-based activities. We also report on the value of IVT in faculty development activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The concept of remote clinical examination has taken many forms. Previous researchers have attempted to use videoconferencing, networked webcams with propriety software and Telehealth equipment. The use of videotaping may also be considered a form of remote examination if the encounter is viewed and scored at a later time …”
Section: Introductionmentioning
confidence: 99%
“…The concept of remote clinical examination has taken many forms. Previous researchers have attempted to use videoconferencing, networked webcams with propriety software and Telehealth equipment. The use of videotaping may also be considered a form of remote examination if the encounter is viewed and scored at a later time …”
Section: Introductionmentioning
confidence: 99%
“…There were no differences between groups in the students' overall evaluation of the examination experiences, and most WebOSCE students found the method enjoyable, reporting it to be a fair test of their skills. Bulik et al 13 explored the use of videoconferencing as a means for community preceptors to assess the interaction of third-year medical students with SPs on clinical performance examinations. They found that an equivalent, although not identical, testing environment for students and evaluators could be facilitated by videoconferencing.…”
Section: Introductionmentioning
confidence: 99%